MULTIFACTOR AUTHENTICATION MEMBUKA KUNCI PINTU RUMAH MENGGUNAKAN IMAGE PROCESSING, FINGERPRINT DAN APLIKASI TELEGRAM UNTUK NOTIFIKASI - Laxsmi Devy (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
The front door serves as the primary entry point to a home and is typically secured with a standard lock. However, such locks have drawbacks, including the risk of the key being forgotten or lost, as well as the ease with which standard keys can be duplicated. Without a CCTV system, homeowners remain unaware of which family members are accessing the house. This system utilizes the Telegram app to enable homeowners to identify family members entering the house. The multi-factor authentication system for unlocking the door combines image processing and fingerprint recognition technologies. It employs a webcam to automatically detect and recognize the user's face using an OpenCV-based algorithm, followed by fingerprint verification via an R307 sensor. An ESP32 microcontroller acts as the controller, processing authentication results and activating a relay to release the solenoid door lock once the user is verified. An I2C LCD displays access status, while a buzzer serves as an audible indicator. The system also features real-time notifications via Wi-Fi using Telegram, allowing homeowners to monitor access activity remotely. Test results demonstrate that the system operates effectively, providing a high level of security through two layers of biometric verification that are difficult to forge.